The determinants of household-level well-being in Northern Ghana - Zereyesus, Yacob A.; Shanoyan, Aleksan; Ross, Kara; Amanor-Boadu, Vincent (My University, 2017)
Empirical analysis of the physical well-being at the household level was conducted for a sample of households in Northern Ghana using a Multiple Indicators Multiple Causes model. Physical well-being was indicated by the number of stunted children, number of wasted children, and number of underweight women. Results suggest that well-being at the household level is indeed represented by the latent variable and can be conceptualized in much the same way as the well-being of the individuals who constitute the household. Results show that the literacy of father and the number of dependents are associated with the largest shift in the underlying household’s physical well-being. Locale and the household assets were also significantly associated with the collective underlying latent variable. The variability in household physical well-being is explained more by the number of stunted children in the household than any of the other indicators of household well-being. © 2016 The Author(s).
Citation: Zereyesus, Y. A., Shanoyan, A., Ross, K. L., & Amanor-Boadu, V. (2016). The determinants of household-level well-being in Northern Ghana. Development Studies Research, 3(1), 1-10. doi:10.1080/21665095.2016.1229128
Keywords: Household Analysis; Mimic Model; Stunting; Underweight; Wasting; Well-Being